2020
DOI: 10.21203/rs.3.rs-34465/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical features of Japanese patients with exacerbations of chronic obstructive pulmonary disease

Abstract: BackgroundExacerbations are critical events in chronic pulmonary obstructive disease (COPD). The frequency of COPD exacerbations is associated with the prognosis, including mortality, but no useful biomarker has been established.MethodsThe present retrospective study investigated 481 COPD patients. Clinical features in the stable period were compared between patients who experienced severe exacerbation (n=88, 18.3%) and those who never experienced severe exacerbation (n=393, 81.7%). In the patients who experie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…For example, low-level physical activity, percent predicted forced expiratory volume in one second (%FEV 1 ), 6-minute walk distance, body mass index (BMI), and a high frequency of exacerbations are significantly associated with mortality in COPD patients 3,4 . We and others have also reported that low-level pulmonary function, exercise tolerance (including 6-minute walk distance and exercise-induced desaturation), and BMI are correlated with a high frequency of exacerbations [5][6][7][8] , indicating that evaluations of exercise tolerance and body composition, in addition to pulmonary function, are important for predicting the clinical course of COPD.…”
Section: Introductionmentioning
confidence: 64%
“…For example, low-level physical activity, percent predicted forced expiratory volume in one second (%FEV 1 ), 6-minute walk distance, body mass index (BMI), and a high frequency of exacerbations are significantly associated with mortality in COPD patients 3,4 . We and others have also reported that low-level pulmonary function, exercise tolerance (including 6-minute walk distance and exercise-induced desaturation), and BMI are correlated with a high frequency of exacerbations [5][6][7][8] , indicating that evaluations of exercise tolerance and body composition, in addition to pulmonary function, are important for predicting the clinical course of COPD.…”
Section: Introductionmentioning
confidence: 64%
“…Patients with COPD suffer from exacerbation, reduced quality of life, and increased morbidity and mortality. [1][2][3] Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is mainly associated with neutrophilic inflammation; however, predominant eosinophilic airway inflammation has been reported in a subset of patients with COPD. [4][5][6] Up to 40% of patients with COPD have an eosinophilic phenotype of COPD, defined as peripheral blood eosinophil (PBE) counts ≥ 2%.…”
Section: Introductionmentioning
confidence: 99%